Financial Incentives and Students Achievement: A Qualitative Study on Students' Success in Engineering Program - NUR HIDAYAH MOHAMED YUNUS; TS. DR. AINI NAZURA PAIMIN (International ABEC, 2021)
Issues on retention in higher education have been discussed from variety of perspectives and is complex to be understood. There is an urge need to understand how some engineering students could survive until final year while the others not. Financial incentive is suggested as an important external motivational factor that could influence student’s achievement in the program. These beliefs have led to the use of financial incentives (along with the intrinsic incentives already presumed to be present) to motivate students. This study explores the role of financial incentives in motivating positive emotions of students in collectivist context, Malaysia. The main aim of this study is to qualitatively explore how financial incentive contributes to students’ academic achievement. 24 final year engineering undergraduates were purposely selected from four Malaysian Technical Universities Network (MTUN) who obtaining a CGPA of at least 3.60 and above were selected as research informants. Data were collected using semistructured interviews, integrated with two creative methods namely graph sketching and photo-card activity. Data were analysed using a thematic coding approach and the coding process was assisted using Atlas.Ti software. Findings of the study discussed how education loan and scholarship play role in.